The Puzzling Persistence of the Distance Effect on Bilateral Trade - Disdier, Anne-Célia; Head, Keith (The Review of Economics and Statistics, 2008)
One of the best-established empirical results in international economics is that bilateral trade decreases with distance. Although well known, this result has not been systematically analyzed before. We examine 1,467 distance effects estimated in 103 papers. Information collected on each estimate allows us to test hypotheses about the causes of variation in the estimates. Our most interesting finding is that the estimated negative impact of distance on trade rose around the middle of the century and has remained persistently high since then. This result holds even after controlling for many important differences in samples and methods.